Three-dimensional deep geoelectric model of the Tarasivka structure of the Golovanivsk suture zone - T. K. Burakhovich; V. A. Ilyenko; A. M. Kushnir; B. I. Shirkov (Геофизический журнал, 2018)
In 2017 the field simultaneous areal measurements of the external low-frequency natural electromagnetic field of the Earth and the construction of a three-dimensional deep resistivity distribution in the crust of the Tarasivka structure (48032' N, 30037' E) were performed in the central part of the Yatran Block of the Golovanivsk suture zone. The analysis of experimental data (the curves of deep magnetotelluric sounding for a period of 10—10000 s and the complex induction parameters for periods of 20—6900 s) indicates a complex three-dimensional situation, which involves the presence of a nearsurface and possibly deep conductivity anomalies. According to the results of three-dimensional modeling, the Tarasivka structure is fragmentarily manifested as a low resistivity, the conductive zones with different resistivity cross it in a sublatitudinal direction, in which the lowest values from 10 Ohm·m in the south to 100 Ohm·m in the north are in its contour. In the vertical section it can be represented in as several layers: the first one is the conductor with ρ=10ч250 Ohm·m — from the surface to 10 m (south of 48030ў) to 100 m (north of 48030ў), most likely linked not only with high electrical conductivity of surface sediment deposits, but also with the zones of disintegration of rocks of the basement; the second one is a high resistivity layer with ρ=10000 Ohm·m — from 100 m to 2 km, possibly it is represented by the uniform non-differentiated thickness; the third layer is the electrical conductor with ρ=10ч250 Ohm∙m from 2—3 km to 10 km, probably linked with the special composition of the earth’s crust at these depths (graphitization, sulfidization, etc.) or fluidization of different origins, more often it is considered according to the modern data that the nature of the conductive anomalies is the result of the joint influence of the electron and ion types of electrical conductivity.